Be Not Far From Me: The Oldest Love Story: Legends from the Bible - Kimmel, Eric A. (Simon & Schuster Inc., 1998)
Be Not Far From Me is a thought-provoking epic that brings past, present, and future together in the ongoing love story between God and humanity.
Keywords: Bible Stories; Juvenile Non-Fiction; Religion